Effects of Planting Date and Growth Hormone on Growth and Yield of Cauliflower - Rahman, MA; Imran, M; Ikrum, M; Rahman, MH; Rabbani, MG (Journal of Environmental Science and Natural Resources, 2017)
An experiment was conducted at the Horticulture Farm of Bangladesh Agricultural University, Mymensingh, during the period from October 2014 to March 2015 to study the effects of planting date and growth hormone on the growth and yield of cauliflower. The experiment consisted of two factors; Factor A: Three planting dates, such as P1: Planting on 1 November; P2: Planting on 15 November and P3: Planting on 1 December; Factor B: Four levels of Growth hormone, such as H0: No Hormone (control); H1: 10 ppm IAA (Indole-3 Acetic Acid); H2: 70 ppm GA3 (Gibberellic Acid) and H3: 10 ppm IAA + 70 ppm GA3. The experiment was laid out following Randomized Complete Block Design (RCBD) with three replications. In case of planting date, the highest plant height (63.26 cm), number of leaves per plant (24.13), leaf length (59.26 cm), leaf breadth (19.31 cm) at harvest, curd diameter (22.25 cm), marketable yield per hectare (28.11 t ha-1) were recorded from P2 and the lowest of those parameters were recorded from P3. In case of growth hormone the highest plant height (63.10 cm), number of leaves per plant (23.66), leaf length (59.05 cm), leaf breadth (18.98 cm) at harvest, curd diameter (22.39 cm), marketable yield per hectare (29.88 t ha-1) were recorded from H3 and the lowest of those perameters were recorded from H0. Combination of planting date and growth hormone the highest plant height (65.96 cm), number of leaves per plant (26.42), leaf length (63.64 cm), leaf breadth (20.92 cm) at harvest, curd diameter (25.75 cm), marketable yield per hectare (31.03 t ha-1) were recorded from planting on 15 November and 10 ppm IAA with 70 ppm GA3 (P2H3) and the lowest parameters (21.75 t ha-1) were recorded from planting on 1 December and no hormone (P3H0). It is apparent from the above results that the combination of planting on 15 November and 10 ppm IAA with 70 ppm GA3 (P2H3) was more productive from the other combinations. J. Environ. Sci. & Natural Resources, 9(2): 143-150 2016